THE EFFECT OF EDUCATION USING VIDEO ANIMATION ON ELEMENTARY SCHOOL IN HAND WASHING SKILL - Fauzul Hayat (Universitas Muhammadiyah Kalimantan Timur, 2021)
ABSTRACT This study aims to determine the effect of education using video animation on an elementary school in handwashing technique. The sample in this study was elementary school students class VI Cigabus Serang, Banten. The instrument used in data collection is a validated test instrument. This study uses a quantitative approach with a quasi experimental single group pretest posttest design.The results of the study showed that the pretest revealed knowledge (26,7%) and excellent hand washing skills (8,3%), and in posttest revealed knowledge (70%) and excellent hand washing skills (73,3%). Handwashing health education using video animation was effective to increase the knowledge and skills of school children regarding the proper technique of handwashing in elementary school (p = 0.000) at a significant level α = 0.05. Education using video animation affects handwashing behavior among elementary school students. Keywords: Video animation, Elementary school, Handwashing technique.